Challenges ahead for the European Union - Lámfalussy, Alexandre (Competitio, 2005)
It is a mild understatement that nowadays the EU is navigating in rough waters. Close to half of the member countries of the Euro area are in breach of their fiscal stability commitment – and some of them very substantially. Quite a few heads of government publicly criticise the ECB’s monetary policy. Germany and France are determined to water down the Bolkenstein directive on the implementation of a genuine single market for services (which amount to about two-thirds of the EU’s GDP), to which, incidentally, no major objections had been raised by the governments of the member states during the drafting stage. There is no agreement on the longer term EU budget. Only Ireland, the UK and Sweden accept the free movement of the residents of the ten countries which became members of the EU in May last year.